Garnishee orders as a tax collection tool: a critical review of the South African and Zimbabwean models - Nzombe, Kudzanayi (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
Taxation statues of most jurisdictions contain provisions that deal with defaulting taxpayers. The taxation statutes of Zimbabwe and South Africa have employed the concept of garnishee orders as a method of recovering tax. This method is codified in the respective taxation statutes under the guise of "third party appointments" , or simply "appointment of an agent" . This method is very convenient and expeditious for the tax collection authorities, namely, the Zimbabwe Revenue Authority (ZIMRA) and the South Africa Revenue Service (SARS). Other jurisdictions have also employed this method, with varying degrees of invasiveness into the taxpayers' constitutional rights. The concept of garnishee orders can have negative constitutional implications for the taxpayers in both Zimbabwe and South Africa. In Zimbabwe, compared to South Africa, the tax collection field is not as developed in terms of jurisprudence and the legislation. There are lessons that Zimbabwe could learn from South Africa, considering that the latter has experienced more than two decades of constitutional democracy. Therefore, in order to identify areas for development, the two jurisdictions are critically reviewed, with particular attention to the legislative provisions and case law dealing with garnishee orders in the tax collection context. Approaches employed by other countries in relation to similar concepts and provisions are also analysed. The lessons learned from this analysis could suggest a less invasive method of recovering tax from defaulting taxpayers and an approach to be followed by the tax authorities, ZIMRA and SARS that would allow them to fulfil their responsibilities and mandate with taxpayer-friendly measures.
Keywords: Uncatalogued